Influence of Course Teaching of Life Skills on College Freshmens Knowledge and Attitude to Life Skills and Improving their Psychosocial Capabilities - Marzieh Moghadam; Narges Rostami Gooran; Modaber Arasteh; Narges Shams Alizadeh; Azad Maroofi (Kerman University of Medical Sciences, 2008)
Background & Objective : Students at university are always exposed to a lot of psychological problems during their education due to experiencing new problems and different stresses Thus teaching life skills was added to medical and midwifery freshmens curriculum for the first time in Kurdistan University of Medical Sciences in 2006This study was performed to evaluate the efficacy of the aforementioned program on the students knowledge and attitude to life skills and their psychosocial capabilities improvement Methods : In this quasiexperimental study cases were 51 medical and midwifery freshmen and control group included 42 medical and midwifery students who were in their second semester Data was collected using a questionnaire which its validity and reliability were confirmed Results : The mean scores of the students knowledge and attitude increased significantly in cases in comparison to controls (719 in contrast to 466 P=00001 and 874 in contrast to 590 P=00001 respectively) According to two way ANOVA field of study did not influence on the efficacy of education regarding students knowledge and attitude Mean score of psychosocial capabilities increased significantly only in cases of midwifery group compared to their control group (2475 in contrast to 2014 with p=00001) Conclusion : Teaching life skills to students in a systematic and organized way in a form of single unit course had a significant effect on improvement of students knowledge and attitude to life skills and psychosocial capabilities It is obvious that education should continue for at least one year in order to have constant results